Impact of Information Feedback Strategy on Vehicle Emissions Reduction on Beltways - Wenting Li, Di Han, Xin Huang, Chao Lou (Forest Chemicals Review, 2022)
In recent years, the information feedback strategy plays an important role in the Intelligent Transportation System (ITS). It improves the efficiency of the use of existing road facilities and eases the congestion problem. However, there is not do any work that studies the impact of information feedback on the environmental problems brought by the vehicle emissions. In this paper, we consider the aspect of emissions reduction with information feedback strategy. Firstly, we introduce the feedback strategy applied to the beltway scenarios, this information feedback strategy does not take into account the environment. Secondly, the representative emission model, International Vehicle Emissions (IVE), is selected to estimate the fuel consumption and the emissions of vehicles on beltways. Finally, based on the fuel consumption and the emission model, we evaluate the impact of information feedback strategy on vehicle emissions on beltways. The result shows that strategy can alleviate traffic congestion, improve transport efficiency and reduce polluting gas emissions.